Enhancing Implant Position Accuracy in Guided Implantology: The Role of Drill Play Under Lateral Forces - Vasilios Alevizakos; Yannick Stryga; Constantin vonSee (Clinical and Experimental Dental Research, 2024)
ABSTRACT Objectives This study investigates the impact of drill play on the precision of implant positioning under lateral forces in guided implantology. Materials and Methods An in vitro experiment was conducted using artificial bone blocks and the SIC Invent‐guided surgery implant system. Custom drill guides were designed, and 3D‐printed, using three sleeve types: sleeveless, a big sleeve, and a small sleeve. Drillings were performed with varying lateral forces, and deviations in angle, depth, and position were measured. Results Sleeveless guides showed the highest variability in deviations, with a maximum deviation of 3.92 mm under extreme lateral forces. Big sleeve guides provided the most consistent precision, with deviations ranging from 0.42 to 1.33 mm. Small sleeve guides showed moderate precision, with deviations from 0.14 to 2.17 mm. Higher lateral forces generally increased deviations across all guide types. Conclusions Drill play significantly affects the precision of guided implant drilling, with lateral forces causing deviations from the planned implant position. Big sleeve guides offer better precision under lateral loads compared to sleeveless and small sleeve guides. Strict adherence to the drilling protocol is essential to minimize errors and ensure optimal implant positioning.